Keanekaragaman Tumbuhan Asing Invasif di Kawasan Cagar Alam Gunung Burangrang Kabupaten Subang Jawa Barat - Metha Audrya; Tri Cahyanto; Ana Widiana (Gunung Djati Conference Series, 2021)
Mount Burangrang Nature Reserve is a tropical mountain area with a total width up to 2.700 hectares and is located in Subang and Purwakarta regencies. Mount Burangrang Nature Reserve functions as a protector for the diversity of flora and fauna. However, the protected area is still not spared from the threats which come from outside or within the area. One of the threats is the existence of invasive alien species. It is an alien plant species that is introduced into a non-original ecosystem and brings effects on the ecological field. This study aimed to find out the diversity and distribution of invasive alien species at Mount Burangrang Nature Reserve, Subang Regency, West Jawa in Januari until march 2021. The square transect was chosen as a research method. According to the results, there were seven species of invasive alien plants with a total number of 244 individuals. The diversity index of invasive alien plant species at Mount Burangrang Nature Reserve was categorized as low with a range of values between 0,204-0.819. Meanwhile, the distribution was divided into clumped which owned by six species, Austroeupatoriuminulifolium, Chromolaena odorata, Ageratina Riparia, Calliandracalothyrsus, Musa acuminata, dan Maesopsis eminii and uniform distribution which only one species had Clidemia hirta.